Should ambulant patients be directed to reception or triage first?. Issue 6 (1st November 2001) - Goodacre, S; Morris, F; Tesfayohannes, B; Sutton, G
Abstract : Objectives —Developments in triage have led to patients being directed to triage rather than reception upon arrival in A&E. This study aimed to discover if attending triage or reception first, was preferable in terms of timeliness, clarity and safety. Methods —The study compared two consecutive four week periods during which patients were directed to attend triage first and then reception first. Observers recorded their actions on arrival. Questionnaires recorded the patients' perceptions of each strategy. High priority triage categories were audited during the reception first phase. Results —1850 patients were observed in the triage first phase with a mean door to triage time of 10.6 minutes, triage to reception 5.3 minutes and door to reception 15.8 minutes. A total of 1522 patients were observed in the reception first phase with a mean door to reception time of 0.5 minutes, reception to triage 12.4 minutes and door to triage of 12.9 minutes. Patients were more likely to present to the appropriate place during the reception first phase (88% versus 34%) and reported better understanding of instructions. No case given triage category one or two suffered an adverse outcome resulting from delay associated with attending reception first. Conclusion —Directing patients to attend reception first is timely and less confusing. It is safe provided booking in does not delay assessment by more than 15 minutes.